Znieważający konstytucjonalizm i konstytucjonalizm znieważony. Refleksja socjologiczna na temat kryzysu liberalno-demokratycznego konstytucjonalizmu w Europie pokomunistycznej - Skąpska, Grażyna (Filozofia Publiczna i Edukacja Demokratyczna, 2018)
This paper debates abusive constitutionalism and constitutionalism abused as ways to introduce a fundamental change of political system. Abusive constitutionalism consists in a change of a democratic regime in a less democratic one with the help of democratic means, i.e. democratically legitimized change of the existing constitution, or proclamation of a new constitution, as it recently happened in Hungary. An example of abused constitutionalism presents contemporary Poland. There the fundamental change of democratic regime happens notwithstanding the still binding constitution, as in an oblivion of it, by the means of ordinary laws proclaimed in a rush process by the ruling parliamentary majority. The whole process is steered in an informal way by the chairman of the ruling party. The important context of abusive constitutionalism, and of constitutionalism abused, as I am going to argue, presentst he crisis of liberal constitutionalism, the loss of its motivational force as a moral sign-post in the public sphere. Instead, one observes a retreat to some primordial and emotionally laden conceptualizations of a politically organized community (a Gemeinschaft) where emotions, primary bonds, foundational myths are more important than law and liberal constitution. Such a retreat results from the past but also presents a reaction to the growing complexity of the contemporary world, and involved risks.